(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article analyzes the essence of legal reforms implemented in the conditions of New Uzbekistan based on the concept of an enlightened society, their role in the development of society and their future directions. It also highlights the role of the enlightened approach in the formation of legal consciousness and culture, and its importance in ensuring human rights and freedoms.